New Insights in Therapy for Food Allergy - Cristobalina Mayorga; Francisca Palomares; José A. Cañas; Natalia Pérez-Sánchez; Rafael Núñez; María José Torres; Francisca Gómez (Foods, 2021)
Food allergy is an increasing problem worldwide, with strict avoidance being classically the only available reliable treatment. The main objective of this review is to cover the latest information about the tools available for the diagnosis and treatment of food allergies. In recent years, many efforts have been made to better understand the humoral and cellular mechanisms involved in food allergy and to improve the strategies for diagnosis and treatment. This review illustrates IgE-mediated food hypersensitivity and provides a current description of the diagnostic strategies and advances in different treatments. Specific immunotherapy, including different routes of administration and new therapeutic approaches, such as hypoallergens and nanoparticles, are discussed in detail. Other treatments, such as biologics and microbiota, are also described. Therefore, we conclude that although important efforts have been made in improving therapies for food allergies, including innovative approaches mainly focusing on efficacy and safety, there is an urgent need to develop a set of basic and clinical results to help in the diagnosis and treatment of food allergies.